Toll-Like Receptor Signaling in Severe Acute Respiratory Syndrome Coronavirus 2-Induced Innate Immune Responses and the Potential Application Value of Toll-Like Receptor Immunomodulators in Patients With Coronavirus Disease 2019 - Dai, Jiayu; Wang, Yibo; Wang, Hongrui; Gao, Ziyuan; Wang, Ying; Fang, Mingli; Shi, Shuyou; Zhang, Peng; Wang, Hua; Su, Yingying; Yang, Ming (Frontiers in Microbiology, 2022)
Toll-like receptors (TLRs) are key sensors that recognize the pathogen-associated molecular patterns (PAMPs) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to activate innate immune response to clear the invading virus. However, dysregulated immune responses may elicit the overproduction of proinflammatory cytokines and chemokines, resulting in the enhancement of immune-mediated pathology. Therefore, a proper understanding of the interaction between SARS-CoV-2 and TLR-induced immune responses is very important for the development of effective preventive and therapeutic strategies. In this review, we discuss the recognition of SARS-CoV-2 components by TLRs and the downstream signaling pathways that are activated, as well as the dual role of TLRs in regulating antiviral effects and excessive inflammatory responses in patients with coronavirus disease 2019 (COVID-19). In addition, this article describes recent progress in the development of TLR immunomodulators including the agonists and antagonists, as vaccine adjuvants or agents used to treat hyperinflammatory responses during SARS-CoV-2 infection.